2009
DOI: 10.1007/s12161-009-9092-1
|View full text |Cite
|
Sign up to set email alerts
|

Stable Lead in Milk and Derivates

Abstract: Lead is a heavy metal widely distributed in soil since it is constantly produced by the radioactive decay series of uranium ( 238 U), actinium ( 235 U), and thorium ( 232 Th). The purpose of this research was to determine lead concentrations in fresh milk and derivates of the farms located in the municipalities of Pedra and Venturosa, in the state of Pernambuco, Brazil. The concentration of lead varied from 3 to 90 µg L −1 in fresh milk, from 20 to 1,050 µg kg −1 in curdled cheese, and from 6 to 20 µg L −1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
(15 reference statements)
1
2
0
3
Order By: Relevance
“…These results are in agreement with reports from other regions of Brazil [ 22 25 ]. Indeed, it has been suggested that the largest contribution of lead contamination in cow’s milk (74%) in Brazil arises from the metal vessels used to transport milk to the processing plants [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in agreement with reports from other regions of Brazil [ 22 25 ]. Indeed, it has been suggested that the largest contribution of lead contamination in cow’s milk (74%) in Brazil arises from the metal vessels used to transport milk to the processing plants [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…In fresh and pasteurized bovine milk from the Paraíba Valley region, the mean concentrations of Pb have been reported as 0.04 and 0.23 mg/L, while Cd was below detection limits [ 23 , 24 ]. In the Northern state of Pernambuco the concentration of Pb in fresh milk samples varied from 3 to 90 μg/L [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Si se comparan los resultados de este estudio con otras investigaciones llevadas a cabo en América Latina, la variabilidad sigue siendo significativa, incluso dentro del mismo país. En el caso de Brasil, la contaminación por Pb excedió los límites establecidos tanto en la leche cruda como en los derivados de la leche (Silva y col., 2010;Oliveira y col., 2017;Vasconcelos y col., 2019;Gomes y col., 2013). En Puebla, México, el análisis de muestras de leche cruda reveló la presencia de Pb a una abundancia media de 0,03 mg/kg, y a una abundancia media de 0,12 mg/kg.…”
Section: Discussionunclassified
“…El plomo (Pb) se produce con frecuencia por la descomposición radioactiva del uranio y el actinio, y se puede encontrar en el suelo (Silva y col., 2010). Sin embargo, el plomo también puede introducirse en el medio ambiente a través de otras vías, como el uso de equipos que contienen plomo, fertilizantes químicos y pesticidas, o agua contaminada con plomo (Litter, Farías y Armienta, 2009).…”
Section: Introductionunclassified
“…[6] Generally there are many methods to deal with the total amount of essential elements in milk samples. The analytical techniques usually applied to the determination of metals in milk samples are flame atomic absorption spectrometry (FAAS), [7][8][9][10][11][12][13] graphite furnace AAS, [7,9,11,14,15] ICP-OES, [11,16,17] and ICP-MS. [18][19][20][21][22] Moreover, voltametric techniques are also capable of determining elements at trace levels. [23] Fractionation studies for elements are more informative than total element determinations for all types of samples in order to realize bioavailability and toxicity of elements.…”
Section: Introductionmentioning
confidence: 99%